JOURNAL OF GOVERNMENT & POLITICS : Do Productive Government Expenditures Affect Economic Growth? Evidence from Provincial Governments across Indonesia - Rosdiana Sijabat (FISIPOL UMY, 2017)
This study is intended to examine the impacts of productive expenditures on economic growth on the 25 provinces found in Indonesia before fiscal decentralization (covering 1994-1997) and 33 provinces after decentralization over the period 2011-2015.